2016
DOI: 10.15253/2175-6783.2016000100009
|View full text |Cite
|
Sign up to set email alerts
|

Support network and social support for children with special health care need

Abstract: Objective: to understand and identify the support network and social support from the perspective of familiesof children with chronic conditions. Methods: a qualitative study, with content analysis of 134 records, followedby ten semi-structured interviews. Results: the analysis has revealed that the primary caregiver, the mother,participates in a network of limited support, only with the help of her husband, children, grandparents and thechild ́s godparents. They also have a social network through a multidisci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 9 publications
0
6
0
13
Order By: Relevance
“…As seen in this study, a research conducted in 2016 with families of minors with special health needs observed that some respondents reported that there was no aversion on the part of the family regarding the consequential dependences of the child in daily activities (20) .…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…As seen in this study, a research conducted in 2016 with families of minors with special health needs observed that some respondents reported that there was no aversion on the part of the family regarding the consequential dependences of the child in daily activities (20) .…”
Section: Discussionmentioning
confidence: 61%
“…Concerning the Support Network, a study that dealt with social support to children with special health needs (20) revealed that the families reported receiving help from philanthropic institutions as indispensable to improve the child's quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No caso dos profissionais de saúde, estes se ligam às mães/acompanhantes por situações e contextos relacionados ao tratamento e assistência à saúde da criança (15,(19)(20) . Destaca-se REFERÊNCIAS que a equipe de enfermagem são os profissionais que apresentam maior contato com a criança e seus acompanhantes, seguido da equipe médica (15) .…”
Section: Discussionunclassified